Guru dalam Hubungannya dengan Proses Belajar Mengajar - Vika Fitrotul Uyun (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2023)
Teaching-learning activities are the main function and the most strategic effort to realize the institutional goals carried out by the institution. In the context of carrying out these institutional functions and tasks, the teacher places a position as a central figure. This study aims to determine the relationship of teachers to the student learning process. the method in this research is a literature review or literature study, which contains theories that are relevant to the problems in the research conducted by researchers. The role of the teacher in the modern world of education as it is today is increasing from being just a teacher to a director of learning. Consequently, the duties and responsibilities of teachers have become more complex and heavy as well, so that every teacher is expected to be clever in directing student learning activities in order to achieve learning success (academic performance) as set out in the objectives of PBM (Teaching and Learning Process) activities.